Conditional Transfer Programs: Universal Child Allowance implementation for Social Protection in Tucumán, Argentina (2021)
Currently, more than 40% of people living in poverty in Argentina are children and adolescents. In 2009, the Universal Child Allowance for Social Protection (AUH) was created to equalize the rights between children, the ones born on families with formal jobs and those born on families with informal jobs or even unemployed ones. This document analyzes the implementation of the AUH on the national level and it’s focused on the state of Tucumán. The research seeks to reveal the problems associated with poverty and inequality. Analysing the scope of actions that each sub-national jurisdiction has: and generally, this is involved with operations to summon, disseminate and register the beneficiaries of it. Even though the role of the provinces is not relevant in the implementation of this public policy, it does allow reducing the number of actors involved, which tends to limit the incidence of political factors and its management becomes more efficient. Otherwise, the lack of participation of subnational governments in the implementation of the AUH may also constitute a deficiency since it limits the potential for dialogue between jurisdictional levels of government that could contribute to the comprehensiveness of public policies. Finally, recommendations will be presented in order to improve the management of the program and its coordination with other national and local initiatives.